What are the prospects for deploying advanced biofuels in Canada?. (September 2018) - Mondou, Matthieu; Skogstad, Grace; Bognar, Julia
Abstract: This article addresses the prospects for advanced biofuels in Canada by examining whether recommendations of two literatures for overcoming the unfavourable market conditions and policy uncertainty facing advanced biofuels are met in Canada. Our empirical analyses demonstrate the presence of conditions posited by the innovation policy literature. That is, Canadian governments provide financial support for biofuels research infrastructure and private R&D, invest in training highly qualified personnel, and support knowledge creation and mobilization across industry, academia and government. However, our analyses indicate deficiencies in the conditions posited by the policy network and governance literature for policy innovation. The Canadian state's policy analytical capacity, autonomy from industry, and coordination capabilities are low, as is the organizational development of industry actors. Consistent with the recommendations of the policy network and governance literature, we conclude that improving the prospects for the Canadian advanced biofuels sector requires the Canadian government augment its personnel, expertise and budgetary resources for advanced biofuels policymaking, and strengthen its interdepartmental and intergovernmental coordination mechanisms. Greater cooperation between the two organizations representing Canada's advanced biofuels sector is also recommended. Highlights: Canada supports advanced biofuels' deployment through research & training. Canada supports advanced biofuels' knowledge creation & dissemination. Canada needs stronger state policy analytical capacity for advanced biofuels. Canada needs greater governmental coordination for advanced biofuels deployment. Advanced biofuels deployment requires cooperation across biofuel industry organizations.